Capitalism and freedom - Friedman, Milton (Chicago University of Chicago Press, 2002)
How can we benefit from the promise of government while avoiding the threat it poses to individual freedom? In this classic book, Milton Friedman provides the definitive statement of his immensely influential economic philosophy—one in which competitive capitalism serves as both a device for achieving economic freedom and a necessary condition for political freedom. The result is an accessible text that has sold well over half a million copies in English, has been translated into eighteen languages, and shows every sign of becoming more and more influential as time goes on.
Includes bibliographical references and index.
Keywords: Capitalism